Clinical and computed tomography tumour dimension assessments for planning wide excision of injection site sarcomas in cats: how strong is the agreement?. (14th September 2015) - Ferrari, R.; Di Giancamillo, M.; Stefanello, D.; Giudice, C.; Grieco, V.; Longo, M.; Ravasio, G.; Boracchi, P.
Abstract: In injection site sarcoma (ISS) in cats lateral as well as deep margins should be correctly planned for a successful surgical outcome. The discrepancy between clinical and computed tomography (CT) measurements of dimension in resectable tumour has led to possible bias that affects the subsequent surgical dose. The aim of this study was to prospectively investigate the agreement between clinical and CT measurements of dimension in newly diagnosed ISS in cats. Fifty‐three client‐owned cats that underwent both clinical and CT measurements of the length and width of ISS were included. CT measurements showed a tendency towards being larger than clinical dimensions, and this difference increased with increasing tumour size. Based on our results, in further studies focusing on ISS in cats, the kind of assessment used to define tumour dimensions (CT versus clinic) should be declared and specified to properly consider surgical results and prognostic impact of this variable.